The kinetics of uracil-N-glycosylase distribution inside replication foci - Anna Ligasová; Ivo Frydrych; Barbora Piskláková; David Friedecký; Karel Koberna (Scientific Reports)
Abstract Mismatched nucleobase uracil is commonly repaired through the base excision repair initiated by DNA uracil glycosylases. The data presented in this study strongly indicate that the nuclear uracil-N-glycosylase activity and nuclear protein content in human cell lines is highest in the S phase of the cell cycle and that its distribution kinetics partially reflect the DNA replication activity in replication foci. In this respect, the data demonstrate structural changes of the replication focus related to the uracil-N-glycosylase distribution several dozens of minutes before end of its replication. The analysis also showed that very popular synchronisation protocols based on the double thymidine block can result in changes in the UNG2 content and uracil excision rate. In response, we propose a new method for the description of the changes of the content and the activity of different cell components during cell cycle without the necessity to use synchronisation protocols.